MIL-53(Al)-derived bimetallic Pd–Co catalysts for the selective hydrogenation of 1,3-butadiene at low temperature - Lili Liu; Miaoliang Zang; Lei Li; Yunkai Zhang; Leyuan Wang; Xiaojing Zhou; Chunling Xin; Xishi Tai (Scientific Reports)
Abstract Selective hydrogenation of 1,3-butadiene is a crucial industrial process for the removing of 1,3-butadiene, a byproduct of butene production. Developing catalysts with high catalytic performance for the hydrogenation of 1,3-butadiene at low temperatures has become a research hotspot. In this study, bimetallic Pd–Co catalysts supported on Al2O3 derived from MIL-53(Al) at various calcination temperatures were synthesised via the co-impregnation method. These catalysts were structurally characterised using powder X-ray diffraction, thermogravimetric analysis, N2 adsorption–desorption, X-ray photoelectron spectroscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, and inductively coupled plasma optical emission spectroscopy techniques. The characterisations revealed that Pd–Co nanoparticles, averaging 8.5–12.4 nm, were highly dispersed on Al2O3 derived from MIL-53(Al). The effects of reaction temperature, Pd and Co contents, space velocity, and calcination temperature on the catalytic performance for the hydrogenation of 1,3-butadiene were thoroughly investigated. The PdCo/MIL-53(Al)-A700 catalyst exhibited the highest catalytic activity for the hydrogenation of 1,3-butadiene at 40 °C and a space velocity of 900 L/(h·gcat). This catalyst demonstrated a strong synergistic interaction between Pd and Co nanoparticles, resulting in considerably better catalytic performance than the monometallic Pd catalyst under the same conditions. The PdCo/MIL-53(Al)-A700 catalyst achieved superior 1,3-butadiene conversion and total butene selectivity compared to the Pd/MIL-53(Al)-A700 catalyst. In addition, the PdCo/MIL-53(Al)-A700 catalyst maintained its catalytic activity and total butene selectivity after three regenerations in a flow of N2 at 200 °C. This work proposed a new pathway to design efficient and sustainable catalysts for 1,3-butadiene hydrogenation.